Identifikasi Miskonsepsi Mahasiswa Pada Pembelajaran Daring Matematika Kimia Melalui Tes Diagnostik Three Tier Multiple Choice - Rina Elvia; Salastri Rohiat; Sura Menda Ginting (Hydrogen: Jurnal Kependidikan Kimia, 2020)
The aim of this study is to determine the misconceptions of Chemistry Mathematics course participants during online learning in Chemistry Education Study Program, University of Bengkulu in the 2020/2021 academic year. This research starts with an online learning process for 4 meeting using Zoom meeting application and Google Classroom using synchronous and asynchronous methods. The method used to detect misconceptions is to provide a Three tier multiple choice diagnostic test consisting of multiple choice question, clear reasons in the form of an essay, and the level of confidence in answering and giving reasons. The tool used in this research is attest tool in the form of a diagnostic test and non-test tool in the form of an interview. Data collection techniques were conducted through test sheets in the form of a Google Forms application and short interviews about diagnostic tests in the form of videos. Data analysis was conducted on response options, reasons, and confidence in responding. The results showed that online learning had an impact on the misconceptions about Chemistry Mathematics course participants with a range of 0-50% where the highest misconception identification results were found in the application of inverse trigonometric functions by 50%,while 0% misconceptions were obtained in the basic concepts of algebraic functions and conversion of rational equations into a partial fractions.